Dual-emission luminescence thermometry using LaGaO3:Cr3+, Nd3+ phosphors. Issue 28 (6th July 2022) - Mullins, Abbi L.; Ćirić, Aleksandar; Zeković, Ivana; Williams, J. A. Gareth; Dramićanin, Miroslav D.; Evans, Ivana Radosavljević
Abstract : Phosphors for luminescence thermometry La1− x Ga0.99 O3 :Cr0.01, Nd x were synthesised by the solid-state method, structurally characterised using powder X-ray diffraction data, and investigated by ambient and variable-temperature optical measurements. Abstract : A series of La1− x Ga0.99 O3 :Cr0.01, Nd x phosphors (where x = 0.005, 0.01, 0.02) for luminescence thermometry was synthesised by the solid-state method, structurally characterised using powder X-ray diffraction data, and investigated by ambient and variable-temperature optical measurements. The design principle relies on the use of a combination of transition metal and rare earth activator ions such that the excitation and emission wavelengths fall within the near infra-red spectral region, notably in the 'first biological window' that is attractive for potential in vivo applications. The photoluminescence spectra of the compounds feature the characteristic 2 E phosphorescence of Cr 3+ at 729 nm and the 4 F3/2 → 4 I9/2 emission of Nd 3+ around 890 nm. The Nd 3+ emission is quenched at a higher rate than that of Cr 3+ with increasing temperature. Thermometric analysis by monitoring the luminescence intensity ratio (LIR) between the emissions of Cr 3+ and Nd 3+ from 300 K to 650 K shows a quasi-Boltzmann trend, with a maximum relative sensitivity of ∼2% K −1, high absolute sensitivity values over this entire temperature range, excellent temperature resolution of 0.04 K at room temperature, and high stability.